The opinion of sports science professionals for the benefit of statistics: an international web-based survey - Ocakoğlu, Gökhan; Macunluoğlu, Aslı Ceren; Can, Fatma Ezgi; Kaymak, Büşra; Yivlik, Zeynep (The European Research Journal, 2020)
Objectives: The present study, an international web-based survey, was focused on four aims: to obtain sports science professional’s self-reported statistical knowledge levels and how this knowledge varies by research area, to investigate and specify when statistics courses should be taught in sports science education and to identify the key statistical methods relevant to sports science education. Methods: In the present study, sports science professional data obtained by a web-based survey. Participants were selected randomly from the PubMed (www.ncbi.nlm.nih.gov) database for the years 2010-2018 using the keywords “school of sports science, faculty of sports science, sports faculty” by screening the sports science journals. Therefore, the participants were determined by searching the keywords in the corresponding or the first author’s address information of the articles. Results: The results indicate that while sports science professionals emphasize statistics education and the participants also believe that taking a statistics course is useful for their occupation. A statistics education should also emphasize the necessity of statistical consultation. Conclusions: Our study provides information regarding self-reported levels of statistical knowledge of sports science professionals by research area and academic position, and provides guidance regarding the ideal semester for administering a statistics course.